Pengaruh Burnout terhadap Work Engagement Karyawan melalui Perceived Organizational Support sebagai Variabel Mediasi - Marcelina, Savira Alviolita; Archianti, Puti (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2024)
This research aims to test the effect of burnout on work engagement with perceived organizational support as a mediating variable. This research uses a quantitative approach with a mediation test model, with a sample size of 230 employees of PT. X in Purwakarta Regency selected through purposive sampling. Burnout is measured using the MBI (Maslach Burnout Inventory) scale, work engagement is measured using the UWES-9 (Utrecht Work Engagement Scale), while the tool for measuring perceived organizational support uses the SPOS-8 (Survey of Perceived Organizational Support) scale. The results show that perceived organizational support is able to partially mediate. Based on the results obtained, it was concluded that there was an influence of burnout on employee work engagement with perceived organizational support as a mediating variable.